Sao Tome and Principe : Domestic Tax System and Tax Revenue Potential - Farhan, Nisreen (IMF Working Papers; Working Paper ;, 2009)
Sao Tome and Principe is very open and highly depends on imports resulting in high indirect tax revenue. At the same time, the production and export base are very narrow, leaving the authorities with a small domestic tax base. For these reasons, the country compares unfavorably with neighboring economies and other island countries, in terms of domestic revenue in percent of GDP. The paper describes the domestic tax system in Sao Tome and Principe and uses cross-country empirical analysis to reach a benchmark tax potential for the country. The paper reaches the conclusion that whether Sao Tome and Principe becomes an oil producer or not, it is more sustainable for it to rely on non-oil domestic revenue-a less volatile and less exhaustible resource-to finance current expenditures. To meet the country's increasing development and social objectives, the authorities need to mobilize sufficient domestic resources. The paper offers a number of fiscal reforms to reach this goal, including implementation of the new tax laws, reduction of exemptions, tax system reforms, and improvement of the tax administration.